Modern Macrolactonization Techniques - Van Hoof, Max; Force, Guillaume; Lebœuf, David (Synthesis, 2023)
The study of macrolactonization processes has been a steady endeavor for synthetic chemists to access macrocycles that are fundamental in the development of numerous high-added-value compounds, notably drugs and fragrances. This field of research is essential as macrolactonizations usually take place at the end of manifold syntheses and chemists need reliable, efficient, and versatile tools to avoid unpredictable results that would lead them to completely redesign their synthetic plan. Here, we highlight the recent methods reported to achieve macrolactonizations towards the formation of both macrolactones and macrodiolides, which feature either Lewis acids, transition metals or organic molecules as activating agents.1 Introduction2 Stoichiometric Carboxylic Acid Activation3 Lewis Acid Catalyzed Reaction4 C–H Activation5 Ring-Expansion Strategy6 Chemoenzymatic Synthesis7 Other Macrolactonization Variants8 Conclusion and Outlook
Keywords: macrolactone; macrodiolide; coupling agent; Lewis acid; C–H activation; ring expansion; chemoenzymatic